PENGARUH LATIHAN PARTNER-RESISTED BACK SQUAT TERHADAP KEKUATAN OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA SMA NEGERI 2 PEKANBARU - Khoirudin, Muhamad; Wijayanti, Ni Putu Nita; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research want to know is there any effect of Partner-Resisted Back Squat exercise toward the strenght of leg mucle of SMAN 2 Pekanbaru man vollyball club, so when do smash, the player get the good jump.This research was experimental research. The population in this research was the man athletes off vollyball SMAN 2 Pekanbaru,while the sample was all of the man athletes SMAN 2 Pekanbaru, the total of 12. The instrument was used leg dynamometer, the purpose is to measure the strenght of leg muscle. The data was analyzed by using statistic to examine the normality with liliefors test on the significant level α 0,05. The submitted hyphothesis was there is a significant effect of Partner-Resisted Back Squat exercise toward the strenght of leg muscle. It shows that the data was normal.Based on the data analysis, t-test showed Tcount was 7,49 and Ttable was 1,796. It means that Tcount > Ttable. Based on the statistic data analysis, the average of preetest was 91,96 and the average of posttest was 94,88. In conclusion, there was a significant effect of Partner-Resisted Back Squat exercise toward the strenght of leg muscle of SMAN 2 Pekanbaru man vollyball club.Keywords : Partner-Resisted Back Squat, the strenght of leg muscle.